Significance of Ultrasound in Diagnosis of Various Musculoskeletal Disorder - Jha, Subash Chandra; Gupta, Mithilesh; Dev, Binit; Regmi, Sudeep; Chaudhary, Ajay; Mahato, Ajay (Birat Journal of Health Sciences, 2020)
Introduction: Ultrasound is a safe, highly cost effective and non-invasive imaging technique without any absolute contraindication. It is also one of the most useful investigations in all medical specialities worldwide. The trend of use of ultrasound in the diagnosis and management of various musculoskeletal disorders (MSD) is tremendously rising in orthopedics practice in Nepal over the last few years. Objectives: The study was conducted to fulfill the existing lacunae in medical literature about use and benefits of ultrasound in context of Nepal. The objective of the study was to assess the effectiveness of ultrasound in the diagnosis of MSD among patients attending orthopedic department. Methodology: All the consecutive patients who visited department of orthopedics and received the diagnosis of MSD and had undergone ultrasonography from February 2017 to February 2019 were included in the study. The effectiveness of ultrasound was evaluated by assessing the correlation between clinical and ultrasound based diagnosis. Results: Out of 420 patients, majorities were female (55%). Out of 6 different anatomical sites identified, maximum patients had problem around wrist and hand (31%) followed by ankle and foot (22.9%). Similarly the most common diagnosis was related to tendon pathology including tendonitis, tenosynovitis and tendinopathy (31.9%). There was statistically significant correlation between ultrasound and clinical diagnosis with P value <0.01. Conclusion: Overuse tendon injury are common pathology around wrist and ankle that can be diagnosed by ultrasound along with many other MSD. The use of ultrasound is gradually widening in scope but has to be performed by the expert to improve the diagnostic accuracy and also to avoid misleading diagnoses. Since there is significant correlation between clinical and ultrasound based diagnosis, it can be beneficial even for young doctors for making effective diagnosis of MSD.